Asphalt-based foam carbon and preparation method thereof

By chemically modifying and multi-step treatment of the polyurethane foam template, asphalt-based foam carbon with high porosity and high mechanical strength was prepared, which solved the problems of uneven structure and insufficient mechanical properties of traditional foam carbon, and was suitable for a variety of application scenarios.

CN119797334AActive Publication Date: 2025-04-11CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510204074.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-11
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

When traditional foam carbon directly liquefies residues, there are problems of uneven bubble structure and insufficient mechanical properties when using coal to liquefy residues, making it difficult to achieve high porosity and high mechanical strength at the same time.

Method used

The preparation method of asphalt-based foam carbon is adopted to enhance the mechanical strength and pore structure uniformity of asphalt-based foam carbon by chemical modification of polyurethane foam templates, multi-step impregnation, oxidation curing and high-temperature carbonization treatment.

Benefits of technology

It has achieved high porosity, low density and high mechanical strength of asphalt-based foam carbon, and has performance suitable for gas storage, pollutant capture and other scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005284008780000071
    Figure BDA0005284008780000071
  • Figure BDA0005284008780000081
    Figure BDA0005284008780000081
Patent Text Reader

Abstract

The invention belongs to the technical field of coal chemical industry, petrochemical industry and carbon materials, and particularly relates to asphalt-based foam carbon and a preparation method thereof. The preparation method comprises the following steps: (S1) impregnating polyurethane foam in a phenolic resin solution, and then drying to obtain polyurethane modified foam; (S2) dissolving asphalt in an organic solvent to form an asphalt solution; (S3) dipping the polyurethane modified foam into the asphalt solution, and then drying to obtain asphalt-loaded polyurethane modified foam; (S4) carrying out oxidation curing on the asphalt-loaded polyurethane modified foam to obtain composite foam; and (S5) carrying out carbonization treatment on the composite foam to obtain the asphalt-based foam carbon. According to the method, the high-added-value foam carbon is prepared from the direct coal liquefaction residues, and the obtained foam carbon has the advantages of high porosity, low density and high mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical fields of coal chemical industry, petrochemical industry and carbon material, and particularly relates to a pitch-based foamed carbon and a preparation method thereof. Background Art

[0002] In the context of global energy shortage, direct coal liquefaction technology is an important means of clean utilization of coal, and the efficient utilization of its byproduct, direct coal liquefaction residue (DCLR), has become the key to improving the comprehensive utilization rate of coal resources. DCLR is rich in unconverted organic matter, which makes it possible to prepare high value-added materials.

[0003] Carbon foam, as a porous carbon material, has shown potential for application in many fields with its unique foam structure and excellent performance. However, traditional carbon foam preparation methods, such as supercritical foaming, have problems such as uneven pore structure and performance degradation caused by inorganic interference when using DCLR. Although the template method can improve the pore structure, the mechanical strength of the carbon foam produced needs to be improved.

[0004] Considering that porosity and mechanical strength are the core indicators of foam carbon performance. High porosity is crucial for enhancing adsorption capacity and reducing material density, and is suitable for gas storage, pollutant capture and other scenarios; while high mechanical strength is the basis for applications such as structural materials and catalyst carriers. Therefore, it is particularly important to develop a foam carbon that can combine DCLR resources and has both high porosity and high mechanical strength. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of uneven pore structure and insufficient mechanical properties of foamed carbon mentioned in the background technology, and to provide a method for preparing foamed carbon with high porosity, low density and high mechanical strength.

[0006] In order to achieve the above object, the present invention provides a method for preparing asphalt-based foamed carbon in a first aspect, comprising the following steps:

[0007] (S1) immersing the polyurethane foam in an ethanol solution of a phenolic resin, and then drying to obtain a polyurethane modified foam;

[0008] (S2) dissolving asphalt in an organic solvent to form an asphalt solution;

[0009] (S3) immersing the polyurethane modified foam in the asphalt solution, followed by drying to obtain an asphalt-loaded polyurethane modified foam;

[0010] (S4) oxidatively curing the asphalt-loaded polyurethane modified foam to obtain a composite foam;

[0011] (S5) Carbonizing the composite foam to obtain asphalt-based foamed carbon.

[0012] The second aspect of the present invention provides a pitch-based foamed carbon obtained by the above preparation method.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] 1. The present invention increases the adsorption capacity of the template to the asphalt solution by chemically modifying the template; at the same time, the two-step impregnation, oxidative curing and high-temperature carbonization steps increase the mechanical strength of the asphalt-based foamed carbon, ultimately making the asphalt-based foamed carbon of the present invention have high mechanical strength on the basis of high open porosity and low density.

[0015] 2. The present invention obtains an asphalt-based foam carbon with adjustable pore structure, density and compressive strength by adjusting the pore size of the polyurethane foam template, the concentration of the asphalt solution and the carbonization conditions. DETAILED DESCRIPTION

[0016] The present invention is further described below by means of specific embodiments. The embodiments of the present invention are only used as illustrations of the present invention and do not mean that the scope of the present invention is limited thereto.

[0017] The method for preparing asphalt-based foamed carbon provided by the present invention comprises the following steps:

[0018] (S1) immersing the polyurethane foam in a phenolic resin solution, followed by drying to obtain a polyurethane modified foam;

[0019] (S2) dissolving asphalt in an organic solvent to form an asphalt solution;

[0020] (S3) immersing the polyurethane modified foam in the asphalt solution, followed by drying to obtain an asphalt-loaded polyurethane modified foam;

[0021] (S4) oxidatively curing the asphalt-loaded polyurethane modified foam to obtain a composite foam;

[0022] (S5) Carbonizing the composite foam to obtain asphalt-based foamed carbon.

[0023] In some embodiments, in step (S1), the polyurethane foam is a cuboid with a pore size of 30-60 PPI and a size of (1-10)×(1-4)×(1-4) cm 3 , to act as a foam carbon template, the pore size of which is closely related to the subsequent asphalt impregnation amount and the strength of the prepared foam carbon; the size of the size is determined by the size of the subsequent carbonization equipment.

[0024] Furthermore, the polyurethane foam can be washed with deionized water and anhydrous ethanol in sequence before use to remove impurities on the polyurethane foam.

[0025] In step (S1), the solvent of the phenolic resin solution is selected from at least one of ethanol, acetone, methanol, toluene and xylene, preferably ethanol.

[0026] Furthermore, the content of phenolic resin in the phenolic resin solution is 5-10 wt.%.

[0027] In step (S1), the phenolic resin solution is dried after impregnation to prevent the influence of moisture on the phenolic resin solution. In some embodiments, the drying temperature is 100-120° C. and the drying time is 1-12 hours.

[0028] The present invention finds that by using a phenolic resin solution to chemically modify the polyurethane foam template, the adsorption amount of the template to the asphalt solution in step (S2) is increased.

[0029] In step (S2), the asphalt is dissolved in an organic solvent, and the raw material components are screened according to the principle of like dissolves like, so that components with suitable molecular weight and polarity are dissolved in the organic solvent to form an asphalt solution, and the solid-liquid separation is carried out to remove the large molecular weight and highly polar components therein; in some embodiments, in step (S2), the asphalt is selected from at least one of coal liquefaction asphalt, coal tar asphalt, biomass asphalt or asphalt obtained by cracking of waste plastics.

[0030] The organic solvent is selected from at least one of toluene, cyclohexane, tetrahydrofuran, xylene, pyridine or kerosene.

[0031] Furthermore, the concentration of the asphalt solution in the asphalt solution will affect the effect of asphalt impregnation. The weight ratio of the asphalt to the organic solvent is 1:(2-3), and they are fully stirred at ambient temperature, such as stirring for 1-24 hours.

[0032] In step (S3), the polyurethane modified foam is immersed in the asphalt solution. The specific operation is to squeeze the polyurethane foam multiple times and use the rebound of the polyurethane foam to fully soak the asphalt solution so that the inner and outer parts of the polyurethane foam are evenly adhered to the asphalt solution, and then dried to remove the toluene solution; in some embodiments, in step (S3), the drying temperature is ambient temperature (e.g., 10-40°C), and the drying time is 24-72h.

[0033] In step (S4), the obtained asphalt-loaded polyurethane modified foam is subjected to an oxidative curing treatment, for example, placed in a tubular cracking furnace for oxidative curing treatment, so as to increase the cross-linking between asphalt molecules and form a more stable network structure, thereby improving the thermal stability and mechanical strength of the asphalt and reducing shrinkage and cracking during the subsequent carbonization process; in some embodiments, in step (S4), the oxidative curing conditions are: in an air atmosphere, the asphalt-loaded polyurethane modified foam is heated at 1-5°C·min -1 The heating rate is from ambient temperature to 200-450℃, and kept at this temperature for 0.5-2h, and finally cooled to ambient temperature.

[0034] In step (S5), the composite foam obtained after oxidative curing is subjected to carbonization treatment, for example, by being placed in a tubular pyrolysis furnace for carbonization treatment; in some embodiments, in step (S5), the carbonization treatment conditions are: in an inert gas atmosphere, the composite foam is heated at 1-5°C·min -1 The heating rate is from ambient temperature to 650-1050℃, and kept at this temperature for 0.5-2h, and finally cooled to ambient temperature.

[0035] The second aspect of the present invention provides a pitch-based foamed carbon obtained by the above preparation method.

[0036] In some embodiments, the asphalt-based foamed carbon has a pore size of 400-550 μm, an open porosity of 97-98%, and a density of 0.03-0.05 g / cm 3 It has a highly open pore structure and its compressive resistance can reach 0.6-1.2MPa.

[0037] The present invention will be described in detail below through specific examples. In the following examples and comparative examples:

[0038] The coal liquefaction asphalt comes from Shenhua Coal to Oil Chemical Company;

[0039] The pore size and pore structure are measured by scanning electron microscopy (SEM); wherein the pore structure is a honeycomb-like structure, and the pore structure is determined to be highly open or uneven by observing and measuring the size of the pores under the field of view under SEM;

[0040] The open porosity is determined by density measurement, for example, by measuring the mass of a specific volume of carbon foam in a dry state and in a state saturated with a liquid;

[0041] The compressive strength is calculated by pressure testing the carbon foam of a fixed volume and cross section.

[0042] Example 1 (A1)

[0043] (S1) washing the polyurethane foam with deionized water and anhydrous ethanol, immersing the foam in an ethanol solution of a phenolic resin, and then drying the foam in an air drying oven to obtain a polyurethane modified foam; wherein:

[0044] The size of the polyurethane foam is 2×2×2 cm 3 , aperture is 50PPI;

[0045] The content of phenolic resin in the ethanol solution of phenolic resin is 8wt.%;

[0046] The drying temperature is 105° C. and the drying time is 2 hours.

[0047] (S2) slowly adding asphalt into an organic solvent and mixing thoroughly to form an asphalt solution; wherein,

[0048] The asphalt is coal liquefaction asphalt, and the amount used is 10g;

[0049] The organic solvent is toluene, and the amount used is 30ml;

[0050] The mixing temperature is 25° C. and the mixing time is 2 h.

[0051] (S3) immersing the polyurethane modified foam of step (S1) in the asphalt solution of step (S2), followed by drying to obtain asphalt-loaded polyurethane modified foam; wherein,

[0052] The drying temperature is 25° C. and the drying time is 48 h.

[0053] (S4) in an air atmosphere, oxidatively curing the asphalt-loaded polyurethane modified foam of step (S3) in a tubular cracking furnace to obtain a composite foam; wherein:

[0054] The oxidative curing conditions include: heating to 300° C. at 2° C. / min, maintaining for 1 hour, and then cooling.

[0055] (S5) in a nitrogen atmosphere, carbonizing the composite foam of step (S4) at high temperature in a tubular pyrolysis furnace to obtain asphalt-based foamed carbon; wherein,

[0056] The high temperature carbonization conditions include: heating to 800° C. at 2° C. / min, maintaining for 1 hour, and then cooling.

[0057] Example 2 (A2)

[0058] Refer to Example 1, the only difference is:

[0059] In step (S1),

[0060] The size of the polyurethane foam is 5×3×3 cm 3, aperture is 60PPI;

[0061] The content of phenolic resin in the ethanol solution of phenolic resin is 9wt.%;

[0062] The drying temperature is 110° C. and the drying time is 6 hours.

[0063] In step (S2),

[0064] The content of the asphalt is 15g;

[0065] The content of the organic solvent is 40ml;

[0066] The mixing temperature is 25° C. and the mixing time is 12 h.

[0067] In step (S3),

[0068] The drying temperature is 25° C. and the drying time is 24 hours.

[0069] In step (S4),

[0070] The oxidative curing conditions include: heating to 400° C. at 3° C. / min, maintaining for 1.5 hours, and then cooling.

[0071] In step (S5),

[0072] The high temperature carbonization conditions include: heating to 900° C. at 3° C. / min, maintaining for 1.5 hours, and then cooling.

[0073] Example 3 (A3)

[0074] Refer to Example 1, the only difference is:

[0075] In step (S1),

[0076] The size of the polyurethane foam is 1×1×1 cm 3 , aperture is 45PPI;

[0077] The content of phenolic resin in the ethanol solution of phenolic resin is 10wt.%;

[0078] The drying temperature is 120° C. and the drying time is 12 hours.

[0079] In step (S2),

[0080] The amount of asphalt is 5g;

[0081] The amount of the organic solvent is 10 ml;

[0082] The mixing temperature is 25° C. and the mixing time is 24 h.

[0083] In step (S3),

[0084] The drying temperature is 25° C. and the drying time is 72 h.

[0085] In step (S4), the oxidative curing conditions include: heating to 200°C at 1°C / min, maintaining for 0.5h and then cooling.

[0086] In step (S5), the high temperature carbonization conditions include: heating to 650°C at 1°C / min, maintaining for 0.5h and then cooling.

[0087] Embodiment 4 (A4)

[0088] Refer to Example 1, the only difference is:

[0089] In step (S1),

[0090] The size of the polyurethane foam is 10×4×4 cm 3 , aperture is 30PPI;

[0091] The content of phenolic resin in the ethanol solution of phenolic resin is 5wt.%;

[0092] The drying temperature is 100° C. and the drying time is 4 hours.

[0093] In step (S2),

[0094] The amount of asphalt is 20g;

[0095] The amount of the organic solvent is 50ml;

[0096] The mixing temperature is 25° C. and the mixing time is 6 h.

[0097] In step (S3),

[0098] The drying temperature is 25° C. and the drying time is 24 h.

[0099] In step (S4), the oxidative curing conditions include: heating to 450°C at 4°C / min, maintaining for 2 hours and then cooling.

[0100] In step (S5), the high temperature carbonization conditions include: heating to 1050°C at 4°C / min, maintaining for 2 hours and then cooling.

[0101] Embodiment 5 (A5)

[0102] Refer to Example 1, the only difference is:

[0103] In step (S1),

[0104] The size of the polyurethane foam is 3×2×2 cm 3 , aperture is 40PPI;

[0105] The content of phenolic resin in the ethanol solution of phenolic resin is 6wt.%;

[0106] The drying temperature is 115° C. and the drying time is 8 hours.

[0107] In step (S2),

[0108] The amount of asphalt used is 12g;

[0109] The amount of the organic solvent is 30 ml;

[0110] The mixing temperature is 25° C. and the mixing time is 18 h.

[0111] In step (S3),

[0112] The drying temperature is 25° C. and the drying time is 36 hours.

[0113] In step (S4), the oxidative curing conditions include: heating to 350°C at 5°C / min, maintaining for 1 hour and then cooling. In step (S5), the high temperature carbonization conditions include: heating to 850°C at 5°C / min, maintaining for 1 hour and then cooling.

[0114] Comparative Example 1 (D1)

[0115] Refer to Example 1, the only difference is:

[0116] In step (S1), the polyurethane foam is directly dried after cutting and washing without being impregnated. The asphalt-based foamed carbon obtained in the above examples and comparative examples was characterized, and the results are shown in Table 1 below.

[0117] Table 1: Characteristics of asphalt-based foamed carbon obtained in Examples and Comparative Examples

[0118]

[0119]

[0120] As shown in Table 1, the asphalt-based foamed carbon prepared by the present invention has a pore size of 400-600 μm, an open porosity of 97-98%, and a carbon density of 0.03-0.05 g / cm 3 The density, highly open cavitation structure and compressive strength of 0.6-1.2MPa indicate that the asphalt is evenly distributed in the foamed carbon and has a stable structure.

[0121] From the comparison of A1-A5 and D1 in Table 1, it can be seen that in the oxidation curing stage, the presence of phenolic resin affects the open porosity of the carbon foam impregnated with phenolic resin compared with the carbon foam not impregnated with phenolic resin. The prepared carbon foam has higher mechanical strength, can prevent pore collapse, and is conducive to the improvement of the open porosity.

[0122] It is noted that the compressive strength of A4 is lower than that of D1. This may be because A4 uses polyurethane with a slightly smaller pore size as a template, and its phenolic resin concentration and content are low; in addition, the subsequent oxidative curing and high-temperature carbonization at too high a temperature and for too long a time will also lead to excessive volatilization of light components in the asphalt, resulting in shrinkage and cracking of the material, which in turn causes the mechanical properties of the foam carbon obtained by A4 to be slightly lower than those of D1.

Claims

1. A method for preparing asphalt-based foamed carbon, characterized in that: The following steps are involved: (S1) immersing the polyurethane foam in a phenolic resin solution, followed by drying to obtain a polyurethane modified foam; (S2) dissolving asphalt in an organic solvent to form an asphalt solution; (S3) immersing the polyurethane modified foam in the asphalt solution, followed by drying to obtain an asphalt-loaded polyurethane modified foam; (S4) oxidatively curing the asphalt-loaded polyurethane modified foam to obtain a composite foam; (S5) Carbonizing the composite foam to obtain asphalt-based foamed carbon.

2. The preparation method according to claim 1, characterized in that: In step (S1), the solvent of the phenolic resin solution is selected from at least one of ethanol, acetone, methanol, toluene and xylene; Preferably, the solvent of the phenolic resin solution is ethanol.

3. The preparation method according to claim 1 or 2, characterized in that: In step (S1), the size of the polyurethane foam is (1-10)×(1-4)×(1-4) cm 3 ; The pore size of the polyurethane foam is 30-60 PPI.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (S1), the polyurethane foam is fully washed with deionized water and anhydrous ethanol and then immersed in a 5-10wt.% phenolic resin solution; In step (S1), the drying temperature is 100-120°C, and the drying time is 1-12 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (S2), the asphalt is selected from at least one of coal liquefaction asphalt, coal tar asphalt, biomass asphalt or asphalt obtained by cracking waste plastics; The organic solvent is selected from at least one of toluene, cyclohexane, tetrahydrofuran, xylene, pyridine or kerosene.

6. The preparation method according to any one of claims 1 to 5, characterized in that In step (S2), the weight ratio of asphalt to organic solvent in the asphalt solution is 1:(2-3); Preferably, the asphalt is coal liquefaction asphalt; Preferably, the organic solvent is toluene.

7. The preparation method according to any one of claims 1 to 6, characterized in that In step (S3), the drying temperature is 10-40°C and the drying time is 24-72h.

8. The preparation method according to any one of claims 1 to 7, characterized in that In step (S4), the oxidative curing conditions include: in an air atmosphere, the asphalt-loaded polyurethane modified foam is heated at 1-5°C·min -1 The heating rate is from ambient temperature to 200-450℃, and kept at this temperature for 0.5-2h, and finally cooled to ambient temperature.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (S5), the high temperature carbonization conditions include: in an inert gas atmosphere, the composite foam is heated at 1-5°C·min -1 The heating rate is from ambient temperature to 650-1050℃, and kept at this temperature for 0.5-2h, and finally cooled to ambient temperature.

10. A pitch-based foamed carbon obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of graphitic carbon foam with high aperture ratio

    CN102134068A

  • Preparation method of carbon / carbon nano tube composite foam adsorption material

    CN104874381A

  • A method of producing carbon foam

    IN201831047019A

  • Manufacturing method of carbon material by using waste of phenolic foam

    KR101667780B1

  • Foam carbonization and resulting foam structures

    US3922334A